Problems of dynamic in mediterranean forests - Quézel, Pierre (Lazaroa, 1983)
The mediterranean forest ecosystems constitute a complex unit which is marked off the Northern and middle European ones by its climate, ecology and management.The ecosystems are related to a climate with estival droughtlasting from 1 to 6 months and the peculiar species which constitute them are generally not worth much.The anthropic pressure exerts especially by grazing and moreover they have been stricken by dramatic fires for many decades. Their large variety related to the bioclimatic and edaphic heterogeneity of the region can explain why the data concerning their functioning and dynamics are still fragmentary. Besides, their ecological and pedological characteristics make uneasy the use of schemes and patterns designed for middle european forests.